Multi-wavelength phase-shifting interferometry based on a two-step phase-shifting phase retrieval algorithm with a color CMOS. (25th June 2020) - Fan, Jinping; Li, Chunjun; Zhang, Jingdan; Cui, Yingjie
Abstract: By combining the advantages of multi-wavelength phase-shifting interferometry and two-step phase-shifting phase retrieval algorithm, a measured phase with high precision and a large measuring range can be retrieved rapidly from three multi-wavelength interferograms with unknown phase shifts, recorded by a single-chip color CMOS. Firstly, two normalized differential interferograms without backgrounds are obtained by means of subtraction followed by normalization between the three color interferograms. Next, the wrapped phases of a single wavelength are retrieved via the Gram–Schmidt orthonormalization approach. Finally, the unambiguous phase of the three synthetic wavelengths can be achieved by subtraction between the wrapped phases of corresponding wavelengths. To reduce the phase noise amplification introduced by the magnification of wavelengths, the phase unwrapping algorithm of reducing the noise of the three- synthetic wavelength to the level of a two-synthetic long wavelength, a single-wavelength, and a two-synthetic short wavelength are implemented in turn. Compared with conventional multi-wavelength phase shifting interferometry, only three interferograms with unknown phase shifts are needed to reconstruct the actual phase of the measured object to a high degree of measurement resolution, and with a large measurement range; this approach would be useful in dynamic phase measurement. Both simulation and experimental results validate the performance of the proposed method.